2023
DOI: 10.1039/d3cp03515h
|View full text |Cite
|
Sign up to set email alerts
|

Energy-conserving molecular dynamics is not energy conserving

Abstract: Molecular dynamics (MD) is a widely-used tool for simulating the molecular and materials properties. It is a common wisdom that molecular dynamics simulations should obey physical laws and, hence, lots...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…We have previously shown that the high quality of the AIQM1 method results in rather accurate IR spectra obtained from MD simulations compared to spectra obtained with a representative DFT (which is also substantially slower; see example in Figure ) or a semiempirical QM method.…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that the high quality of the AIQM1 method results in rather accurate IR spectra obtained from MD simulations compared to spectra obtained with a representative DFT (which is also substantially slower; see example in Figure ) or a semiempirical QM method.…”
Section: Simulationsmentioning
confidence: 99%
“…MLatom has a native implementation of MD supporting any kind of model that provides forces, not necessarily conservative . Currently, simulations in NVE and NVT ensembles, based on the velocity Verlet algorithm, are possible.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our related study on learning the sequential information in the dissipative quantum dynamics revealed that the specialized NN models are not necessarily better choices than simpler models such as feed-forward NN used in the GICnet. 43 Long-time trajectory propagation is a challenge even for traditional MD, especially propagated with 3D-MLPs, 44,45 because the molecules sometimes unphysically explode as we also observed in many reference trajectories during the preparation of the training set (unphysical explosions happen because the 3D-MLP does not describe a dissociation part of PES correctly by severely underestimating the potential energies; 57 we removed such exploding reference trajectories and did not use them for training; see the Supporting Information). Thus, when we trained the preliminary versions of the GICnet models without physical constraints introduced below, we observed that the molecules may explode during long-time MD.…”
mentioning
confidence: 99%
“…The simulations can be performed online using the MLatom@XACS () cloud computing service. MLatom implementation of MD with 3D-MLPs is also publicly available as described in ref .…”
mentioning
confidence: 99%